The influence of new farmer live streamer characteristics on purchase intention: the roles of parasocial interaction and regional cultural differences - Cheng, Guo; Bao, Tiantian; Li, Wenjie; Li, Zirong; Li, Zhenmin; Zu, Xu (Frontiers in Communication, 2025)
IntroductionAgricultural live streaming has emerged as a vital channel for rural development, yet limited research examines how new farmer live streamers’ characteristics influence consumer behavior. Guided by the Stimulus–Organism–Response (S-O-R) framework and parasocial interaction theory, this study investigates how the characteristics of new farmer live streamers shape consumers’ purchase intention in agricultural e-commerce.MethodsFive key streamer characteristics—authenticity, social responsibility, trustworthiness, affinity, and interactivity—were identified through surveys, interviews, and text analyses. Data from 441 valid responses were analyzed using structural equation modeling to test the proposed relationships.ResultsThe findings reveal that authenticity, social responsibility, trustworthiness, and interactivity positively affect purchase intention, whereas affinity shows no significant impact. Parasocial interaction mediates the effects of authenticity, trustworthiness, affinity, and interactivity on purchase intention, but not social responsibility. Additionally, regional cultural differences negatively moderates the relationship between parasocial interaction and purchase intention.DiscussionThese findings provide actionable implications for stakeholders: governments, agricultural enterprises, and new farmer streamers should cultivate essential streamer characteristics, strengthen parasocial connections, and adapt engagement strategies to regional cultural contexts to enhance the effectiveness and sustainability of agricultural live streaming.